1998
DOI: 10.1155/1998/974145
|View full text |Cite
|
Sign up to set email alerts
|

Cell Proliferation Activity and Prognostic Index in Squamous Cell Lung Carcinoma

Abstract: Flow Cytometry (FC) has been incorporated into cancer research in relation to its prognostic value together with histological parameters and TNM stages. We have studied by means of FC the cell cycle of 132 samples from male patients with Squamous Cell Lung Carcinoma (SQCLC). All of the patients received curative surgery and the clinical follow-up was 60 months. The clinical and cytometric parameters were evaluated in order to predict the patients’ outcome. The presence of tumoural recurrence and the tumoural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Some studies of lung cancer that incorporated DNA flow cytometry found that the proliferative activity of DNA aneuploid tumors was higher than that of DNA diploid tumors, [16][17][18] whereas other studies found that there were no differences in proliferative activity between DNA ploidy patterns. 14,19,20 In this study the putative higher proliferative activity of DNA aneuploid tumors could not be proved for NSCLC, even with accurate SPF analysis with the cytokeratin gating method. Previous studies that found DNA diploid tumors to have low proliferative activity may have underestimated the SPF because of the presence of normal cells inside the tumors.…”
Section: Discussionmentioning
confidence: 64%
“…Some studies of lung cancer that incorporated DNA flow cytometry found that the proliferative activity of DNA aneuploid tumors was higher than that of DNA diploid tumors, [16][17][18] whereas other studies found that there were no differences in proliferative activity between DNA ploidy patterns. 14,19,20 In this study the putative higher proliferative activity of DNA aneuploid tumors could not be proved for NSCLC, even with accurate SPF analysis with the cytokeratin gating method. Previous studies that found DNA diploid tumors to have low proliferative activity may have underestimated the SPF because of the presence of normal cells inside the tumors.…”
Section: Discussionmentioning
confidence: 64%
“…[14][15][16][17][18][19] The analysis without gating in our study showed that DNA diploid tumors had significantly lower SPFs than DNA aneuploid tumors, whereas the analysis with CK-gating did not find this difference. In other words, the final interpretation may depend strongly upon whether or not CK-gating is used.…”
Section: Discussionmentioning
confidence: 85%
“…Consequently, the proliferative activity index used in this study could offer a more precise piece of information about the factions of cells in S and G 2 /M phases of cell cycle. However, other studies found that there were no differences in proliferative activity between the DNA ploidy patterns [14,[32][33][34].…”
Section: Discussionmentioning
confidence: 87%